Effects of Rootstock and Harvest Season on the Maturation of Portuguese and Spanish Clones of the Aragonez (syn. Tempranillo) Cultivar (Vitis vinifera L.) Grown Under Tropical Semi-Arid Conditions in Northeastern Brazil: Clone, Rootstock and Harvest Effects on Red Grapes in Tropical Climate - Macedo de Amorim, Francisco (South African Journal of Enology and Viticulture, 2026)
This study evaluated the effects of rootstock and harvest season on the maturation of Portuguese and Spanish clones of the Aragonez (syn. Tempranillo) grapevine cultivar (Vitis vinifera L.) grown under tropical semi-arid conditions in the São Francisco Valley, Brazil. Ten clones grafted onto four rootstocks were assessed over four harvests (two per year) across two consecutive years. Yield remained stable across all clone-rootstock combinations, regardless of the season. However, significant differences in physicochemical traits, organic acid profiles, phenolic composition, and colour parameters were observed. Spanish clones, particularly E24 and E51, consistently exhibited higher levels of anthocyanins, total phenolics, and condensed tannins, suggesting greater suitability for deeply colored and bodied wines. Among Portuguese clones, 60EAN and 110JBP stood out for their favourable acidity and anthocyanin profiles. Rootstock effects varied with season, with SO4 and IAC572 enhancing phenolic maturity, especially in second-semester harvests under warmer and drier conditions. Principal component analyses confirmed strong interactions among clone, rootstock, and harvest timing, highlighting the complexity of genotype × environment × management relationships in tropical viticulture. These findings support the strategic use of diverse clone-rootstock combinations and flexible harvest scheduling to optimise grape quality and expand wine style possibilities in emerging warm-climate regions.